PENGARUH PELAYANAN TERHADAP KEPUASAN KONSUMEN DI BENGKEL RASWO SOLO BARU - Iswanto, Andrian; Pratama, Topik; Perdana, Krisna Adhi; Vernanda, Ayu; Imania, Khofifah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
In order to improve the quality of service at Raswo's workshop, this study aims to determine customer satisfaction at Raswo's Solo Baru Workshop. Research is reviewed from the quality of service and services provided. This research was also conducted to identify other factors that influence the decline in customer satisfaction at Bengkel Raswo Solo Baru. To measure customer satisfaction, explanatory research or often called causal research is used. The population of this study were all customers of Raswo Solo Baru Workshop with a sample size of 30 customers with 24 questions on each questionnaire sheet. Based on the data results, it can be seen that service and service have a positive effect on customer satisfaction. This is indicated by the weighted Average Value (NRR) of 3.8567 from the range (1.00-4.00) and the value of the Community Satisfaction Index (IKM) resulting in a score of 96.418 from the range (25.00-100.00).